Predictors of symptomatic intracranial haemorrhage in patients with an ischaemic stroke with neurological deterioration after intravenous thrombolysis. Issue 8 (27th February 2018) - James, Brandon; Chang, Andrew D; McTaggart, Ryan A; Hemendinger, Morgan; Mac Grory, Brian; Cutting, Shawna M; Burton, Tina M; Reznik, Michael E; Thompson, Bradford; Wendell, Linda; Mahta, Ali; Siket, Matthew; et al.
Abstract : Objectives: Early neurological deterioration prompting urgent brain imaging occurs in nearly 15% of patients with ischaemic stroke receiving intravenous tissue plasminogen activator (tPA). We aim to determine risk factors associated with symptomatic intracranial haemorrhage (sICH) in patients with ischaemic stroke undergoing emergent brain imaging for early neurological deterioration after receiving tPA. Methods: We abstracted data from our prospective stroke database and included all patients receiving tPA for ischaemic stroke between 1 March 2015 and 1 March 2017. We then identified patients with neurological deterioration who underwent urgent brain imaging prior to their per-protocol surveillance imaging and divided patients into two groups: those with and without sICH. We compared baseline demographics, clinical variables, in-hospital treatments and functional outcomes at 90 days between the two groups. Results: We identified 511 patients who received tPA, of whom 108 (21.1%) had an emergent brain CT. Of these patients, 17.5% (19/108) had sICH; 21.3% (23/108) of emergent scans occurred while tPA was infusing, though only 4.3% of these scans (1/23) revealed sICH. On multivariable analyses, the only predictor of sICH was a change in level of consciousness (OR 6.62, 95% CI 1.64 to 26.70, P=0.008). Conclusion: Change in level of consciousness is associated with sICH among patients undergoing emergent brain imaging after receiving tPA. In this group of patients, preparation of tPA reversal agents while awaiting brain imaging may reduce reversal times. Future studies are needed to study the cost-effectiveness of this approach.